Comparative Study of Accessibility Standards for Toilets in Special Schools (SLB) in Central Java - Fauzan Ali Ikhsan; Dimas Fadhil Qodryansyah Saputra; Zacklee Hersya Yanuarta; Renny Gloria Simanjuntak (Sinektika: Jurnal Arsitektur, 2026)
This research examines the comparison of toilet accessibility standards in Special Schools (SLB) in Central Java Province against the provisions in the Regulation of the Ministry of Public Works and Housing (Permen PUPR) Number 14 of 2017 and the Americans with Disabilities Act (ADA). The background of this research is based on the importance of providing equal sanitation facilities for students with special needs, considering accessibility is a crucial aspect in supporting inclusivity and independence in the educational environment. The urgency of this research lies in the effort to identify the gap between the existing facility conditions and the applicable national and international standards. The research method used is descriptive-comparative through field observation, documentation, and comparative analysis of standards at several Special Schools (SLB) in the Central Java region. Each facility is evaluated based on spatial planning parameters, circulation, equipment dimensions, and supporting elements for people with disabilities. The research results show that although some special schools have adopted the principles of inclusive design, most toilet facilities have not fully met the minimum standards of Permen PUPR No. 14/2017, and even lag behind the provisions in the ADA, particularly in terms of corridor width, door width, door opening direction, and toilet area. This finding underscores the need for continuous evaluation and improvement of accessible facilities in educational environments to align with the principles of universal design and support equality for all students.